Synthesis Of Nano Ni-Mo/γ-Al2O3 CatalystSynthesis Of Nano Ni-Mo/γ-Al2O3 Catalyst - Mohamed, Abdul-Halim A. K.; Atta, Hawraa H. (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
Nano γ-Al2O3 support was prepared by co-precipitation method by using different calcination temperatures (550, 600, and 750) oC. Then nano NiMo/γ-Al2O3 catalyst was prepared by impregnation method were nickel carbonate (source of Ni) and ammonium paramolybdate (source of Mo) on the best prepared nano γ-Al2O3 support at calcination temperature 550 oC. Make the characterizations for prepared nano γ-Al2O3 support at different temperatures and for nano NiMo/γ-Al2O3 catalyst like X-ray diffraction, X-ray fluorescent, AFM, SEM, BET surface area, and pore volume.The Ni and Mo percentages in the prepared nano NiMo/γ-Al2O3 catalyst determined by X-ray fluorescence were 2.924 wt % and 12.9 wt %, respectively. SEM of prepared nano γ-Al2O3 support at calcination temperature 550 oC. The average particles diameter of prepared γ-Al2O3 support determined by AFM at calcination temperatures 550, 600, and 750 oC and for prepared nano NiMo/γ-Al2O3 catalyst at calcination temperature 550 oC.